Technology of calibrated wire production for bearing rolling elements manufacturing - V. V. Belash; Y. I. Kozyreva; Y. S. Belash (Литьë и металлургия, 2023)
The article considers technological schemes of cold‑formed wire production for bearing rolling elements production. Several technological schemes of wire production are considered. The paper presents a step‑by‑step development of drawing technology of alloyed (chromium) bearing steel grade. Problems arising at drawing of bearing steels are described. The reason of formation of “flaking” on the surface of rod is revealed. Ways of solving the problem of unsatisfactory drawing of wire from bearing steel grades are stated.Relevance and novelty of technical and technological solutions of the present work are caused by the absence of production of calibrated wire for manufacturing of rolling elements of bearings on the territory of the Republic of Belarus. The development of this type of production will allow to increase the production of high‑tech products with a deep degree of processing (calibrated wire) for the growth of profitability and efficiency indicators. Creation of production of calibrated wire for manufacturing of rolling elements of bearings will allow to reach new consumers of metal products with increase of added value of finished products.